Preparation method of environment-friendly wear-resistant water-based paint
By performing ultraviolet radiation graft modification on the polyester fiber and mixing it with aqueous epoxy resin, an environmentally friendly wear-resistant water-resistant coating was prepared, which solved the problem of poor wear resistance of epoxy resin coatings and significantly improved the wear resistance and hardness of the coating.
Patent Information
- Application Number
- CN202411474586.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-22
- Publication Date
- 2025-02-28
Smart Images

Figure BDA0005095704880000011 
Figure BDA0005095704880000021 
Figure BDA0005095704880000061
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of coatings, and in particular to a method for preparing an environmentally friendly, wear-resistant water-based coating. Background Art
[0002] At present, the main coatings are solvent-based coatings, which contain more volatile solvents such as toluene, ethyl acetate, acetone, etc. The solvents are easy to volatilize during the curing process, causing great pollution. Therefore, it is of great significance to develop water-based environmentally friendly coatings. Among them, water-based epoxy resin coatings use water as a solvent, which is green and environmentally friendly, has excellent film-forming properties, high strength, and high anti-corrosion properties. However, epoxy resins have poor toughness and poor wear resistance, which limits the practical application of epoxy resins.
[0003] Using high-performance polymer fiber materials to fill and modify epoxy resin is an effective way to improve its mechanical properties. Polyester fiber has high strength, large modulus, good wear resistance, and excellent high temperature resistance. It has a wide range of practical applications in coatings, plastics, rubber and other materials. However, improving the compatibility between polyester fiber and resin matrix is a research difficulty. Summary of the invention
[0004] The invention solves the problem that the mechanical properties of epoxy resin coatings, such as wear resistance, are relatively poor.
[0005] The technical solution provided by the present invention is: a method for preparing an environmentally friendly wear-resistant water-based coating, comprising the following steps:
[0006] Step (1), placing the cleaned and dried polyester fiber in ethanol, stirring, adding benzophenone and styrene sulfonic acid imide monomer, placing under ultraviolet light, carrying out grafting reaction in a nitrogen atmosphere, filtering, washing with xylene, ethanol and water in sequence, and drying to obtain modified polyester fiber.
[0007] The styrene sulfonic acid imide monomer has the following structural formula (I):
[0008]
[0009] Step (2), adding water-based epoxy resin, modified polyester fiber, defoamer, thickener, pigment filler and dispersant into water, and then dispersing to obtain environmentally friendly wear-resistant water-based coating.
[0010] Furthermore, in step (1), the power of the ultraviolet lamp is 100-300W and the wavelength is 360nm.
[0011] Furthermore, in step (1), the mass of benzophenone and styrene sulfonic acid imide monomers is 1.2-2.6% and 20-40% of the mass of the polyester fiber.
[0012] Furthermore, in step (1), the temperature during the grafting reaction is 25-35° C., and the time is 20-40 min.
[0013] Furthermore, in step (2), the mass of the modified polyester fiber is 1-6% of the mass of the waterborne epoxy resin.
[0014] Furthermore, the preparation method of styrene sulfonic acid imide monomer includes: adding taurine and potassium hydroxide to methanol, adding 4-vinylbenzaldehyde after stirring, heating to 50-60°C, performing Schiff base reaction for 3-4h, adding the precipitate to methanol after filtering, and then adding potassium borohydride and water, performing reduction reaction at 20-30°C for 2-3h, distilling under reduced pressure, and recrystallizing the product in 60% ethanol aqueous solution by volume to obtain styrene sulfonic acid imide monomer. The reaction formula is:
[0015]
[0016] Furthermore, the molar ratio of taurine, potassium hydroxide, 4-vinylbenzaldehyde and potassium borohydride is 1:1:(0.9-1.1):(1.2-1.4).
[0017] The technical effect of the invention is: using styrene sulfonic acid imide monomer to carry out ultraviolet radiation grafting modification on polyester fiber, a large number of hydrophilic sulfonate groups and active imino groups are introduced on the fiber surface, which significantly improves the surface hydrophilicity of the polyester fiber and is beneficial to improving the dispersibility of the polyester fiber in water-based epoxy resin coatings. The better the dispersibility, the better the modification effect of the polyester fiber, which is beneficial to reducing the friction mass loss of the epoxy resin paint film, improving the wear resistance, and at the same time can improve the hardness of the paint film.
[0018] The active imino groups on the surface of the modified polyester fiber of the present invention can undergo a curing reaction with the epoxy resin, thereby combining the polyester fiber with the epoxy resin through chemical bonding, thereby enhancing the interfacial bonding force between the polyester fiber and the epoxy resin. When the epoxy resin is subjected to external force, many microcracks are generated inside. The polyester fiber bonded in the resin matrix can absorb and transfer stress, prevent the rapid expansion of the cracks, and exhibit a good toughening effect, thereby improving the tensile strength, elongation at break and impact strength of the epoxy resin. DETAILED DESCRIPTION
[0019] The technical solutions in the embodiments of the present invention are described clearly and completely below. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0020] Example 1
[0021] (1) 30 mmol taurine and 30 mmol potassium hydroxide were added to 80 mL methanol, and 30 mmol 4-vinylbenzaldehyde was added after stirring. The mixture was heated to 50° C. and a Schiff base reaction was performed for 4 h. After filtering, the precipitate was added to 70 mL methanol, and then 42 mmol potassium borohydride and 50 mL water were added. The mixture was reduced at 25° C. for 2 h, and distilled under reduced pressure. The product was recrystallized in an ethanol aqueous solution with a volume fraction of 60% to obtain a styrene sulfonic acid imide monomer.
[0022] (2) Place 10 g of the washed and dried polyester fiber in 80 mL of ethanol, stir, add 0.17 g of benzophenone and 2.7 g of styrene sulfonic acid imide monomer, place under a 200 W ultraviolet lamp with a wavelength of 360 nm, in a nitrogen atmosphere, at 30° C. for grafting reaction for 20 min, filter, wash with xylene, ethanol, and water in turn, and dry to obtain a modified polyester fiber.
[0023] (3) Add 500 g of water-based epoxy resin AR555, 5 g of modified polyester fiber, 1.8 g of defoamer FoamStar ED 2522, 1.3 g of thickener TF-938, 110 g of pigment filler titanium dioxide, and 8.6 g of dispersant BYK-110 to 600 mL of water, and shear and disperse by a high-speed disperser to obtain an environmentally friendly wear-resistant water-based coating.
[0024] Example 2
[0025] (1) 30 mmol taurine and 30 mmol potassium hydroxide were added to 100 mL methanol, and 33 mmol 4-vinylbenzaldehyde was added after stirring, and the mixture was heated to 50° C. to carry out Schiff base reaction for 4 h. After filtering, the precipitate was added to 80 mL methanol, and then 40 mmol potassium borohydride and 50 mL water were added, and reduction reaction was carried out at 20° C. for 3 h. The mixture was distilled under reduced pressure, and the product was recrystallized in an ethanol aqueous solution with a volume fraction of 60% to obtain a styrene sulfonic acid imide monomer.
[0026] (2) Place 10 g of the washed and dried polyester fiber in 80 mL of ethanol, stir, add 0.12 g of benzophenone and 2 g of styrene sulfonic acid imide monomer, place under a 100 W ultraviolet lamp with a wavelength of 360 nm, in a nitrogen atmosphere, at 25° C. for a grafting reaction for 40 min, filter, wash with xylene, ethanol, and water in turn, and dry to obtain a modified polyester fiber.
[0027] (3) Add 500 g of water-based epoxy resin AR555, 10 g of modified polyester fiber, 1.8 g of defoamer FoamStar ED 2522, 1.3 g of thickener TF-938, 110 g of pigment filler titanium dioxide, and 8.6 g of dispersant BYK-110 to 600 mL of water, and shear and disperse by a high-speed disperser to obtain an environmentally friendly wear-resistant water-based coating.
[0028] Example 3
[0029] (1) 30 mmol taurine and 30 mmol potassium hydroxide were added to 80 mL methanol, and 27 mmol 4-vinylbenzaldehyde was added after stirring. The mixture was heated to 60° C. and a Schiff base reaction was performed for 3 h. After filtering, the precipitate was added to 70 mL methanol, and then 40 mmol potassium borohydride and 40 mL water were added. The mixture was reduced at 30° C. for 3 h, and distilled under reduced pressure. The product was recrystallized in an ethanol aqueous solution with a volume fraction of 60% to obtain a styrene sulfonic acid imide monomer.
[0030] (2) Place 10 g of the washed and dried polyester fiber in 80 mL of ethanol, stir, add 0.26 g of benzophenone and 4 g of styrene sulfonic acid imide monomer, place under a 300 W ultraviolet lamp with a wavelength of 360 nm, in a nitrogen atmosphere, at 35° C. for grafting reaction for 20 min, filter, wash with xylene, ethanol, and water in turn, and dry to obtain a modified polyester fiber.
[0031] (3) Add 500 g of water-based epoxy resin AR555, 20 g of modified polyester fiber, 1.8 g of defoamer FoamStar ED 2522, 1.3 g of thickener TF-938, 110 g of pigment filler titanium dioxide, and 8.6 g of dispersant BYK-110 to 600 mL of water, and shear and disperse by a high-speed disperser to obtain an environmentally friendly wear-resistant water-based coating.
[0032] Example 4
[0033] (1) 30 mmol taurine and 30 mmol potassium hydroxide were added to 100 mL methanol, and 30 mmol 4-vinylbenzaldehyde was added after stirring. The mixture was heated to 55° C. and subjected to Schiff base reaction for 4 h. After filtering, the precipitate was added to 60 mL methanol, and then 36 mmol potassium borohydride and 40 mL water were added. The mixture was subjected to reduction reaction at 20° C. for 3 h. The mixture was distilled under reduced pressure, and the product was recrystallized in an ethanol aqueous solution with a volume fraction of 60% to obtain a styrene sulfonic acid imide monomer.
[0034] (2) Place 10 g of the washed and dried polyester fiber in 80 mL of ethanol, stir, add 0.21 g of benzophenone and 3.4 g of styrene sulfonic acid imide monomer, place under a 200 W ultraviolet lamp with a wavelength of 360 nm, in a nitrogen atmosphere, at 30° C. for grafting reaction for 30 min, filter, wash with xylene, ethanol, and water in turn, and dry to obtain a modified polyester fiber.
[0035] (3) Add 500 g of water-based epoxy resin AR555, 30 g of modified polyester fiber, 1.8 g of defoamer FoamStar ED 2522, 1.3 g of thickener TF-938, 110 g of pigment filler titanium dioxide, and 8.6 g of dispersant BYK-110 to 600 mL of water, and shear and disperse by a high-speed disperser to obtain an environmentally friendly wear-resistant water-based coating.
[0036] Comparative Example 1
[0037] (1) Add 500 g of waterborne epoxy resin AR555, 1.8 g of defoamer FoamStar ED 2522, 1.3 g of thickener TF-938, 110 g of pigment titanium dioxide, and 8.6 g of dispersant BYK-110 to 600 mL of water, and perform shear dispersion using a high-speed disperser to obtain an environmentally friendly, wear-resistant waterborne coating.
[0038] Comparative Example 2
[0039] (1) Add 500 g of water-based epoxy resin AR555, 5 g of polyester fiber, 1.8 g of defoamer FoamStarED 2522, 1.3 g of thickener TF-938, 110 g of pigment titanium dioxide, and 8.6 g of dispersant BYK-110 to 600 mL of water, and shear and disperse by a high-speed disperser to obtain an environmentally friendly wear-resistant water-based coating.
[0040] Comparative Example 3
[0041] (1) Place 10 g of washed and dried polyester fiber in 80 mL of ethanol, stir, add 0.17 g of benzophenone and 2.7 g of sodium 4-styrene sulfonate, place under a 200 W ultraviolet lamp with a wavelength of 360 nm, in a nitrogen atmosphere, and perform grafting reaction at 30° C. for 20 min. After filtering, wash with xylene, ethanol, and water in turn, and dry to obtain modified polyester fiber.
[0042] (2) Add 500 g of water-based epoxy resin AR555, 5 g of modified polyester fiber, 1.8 g of defoamer FoamStar ED 2522, 1.3 g of thickener TF-938, 110 g of pigment filler titanium dioxide, and 8.6 g of dispersant BYK-110 to 600 mL of water, and shear and disperse by a high-speed disperser to obtain an environmentally friendly wear-resistant water-based coating.
[0043] 130 g of polyetheramine D230 curing agent was added to the environmentally friendly wear-resistant water-based coatings prepared in the embodiments and comparative examples, and after mixing, the coating was first cured at 70° C. for 4 h and then cured at 130° C. for 2 h to form a paint film.
[0044] The friction mass loss and wear resistance of the paint film were tested according to GB / T 1768-2006. The load was 1kg. The speed was 60r / min. The number of wears was 10,000 times. The hardness of the paint film was tested according to GB / T 6739-2022. The test results are shown in Table 1.
[0045] Table 1 Performance test of paint film
[0046]
[0047] The coating with the curing agent added was cast into a mold, first cured at 70°C for 4 hours, and then cured at 130°C for 4 hours to form a casting, and the tensile properties and impact strength were tested according to GB / T 2567-2021. The test results are shown in Table 2.
[0048] Table 2 Casting performance test
[0049]
[0050] As shown in Table 1, the epoxy resin coating of Comparative Example 1 does not contain polyester fiber, and its friction mass loss is large, which is 57.1 mg, and its wear resistance is poor, and its pencil hardness is only 2H. At the same time, the tensile strength, elongation at break and impact strength of the coating casting are low, and the mechanical properties are poor.
[0051] The modified polyester fiber added to the epoxy resin coating of Examples 1-4 is modified by grafting with styrene sulfonic acid imide monomer by ultraviolet radiation, and a large number of hydrophilic sulfonate groups and active imino groups are introduced on the surface of the polyester fiber, which significantly improves the surface hydrophilicity of the polyester fiber and is beneficial to improving the dispersibility of the polyester fiber in the water-based epoxy resin coating. The better the dispersibility, the better the modification effect of the polyester fiber. In addition, the active imino groups on the surface of the modified polyester fiber can undergo a curing reaction with the epoxy resin, thereby combining the polyester fiber with the epoxy resin through chemical bonding, thereby enhancing the interfacial bonding force between the polyester fiber and the epoxy resin. When the epoxy resin is subjected to external force, many microcracks are generated inside. The polyester fiber bonded in the resin matrix can absorb and transfer stress, prevent the rapid expansion of the cracks, and show a good toughening effect, thereby improving the tensile strength, elongation at break and impact strength of the epoxy resin.
[0052] In Comparative Example 2, unmodified polyester fiber is added, which has poor hydrophilicity and poor dispersibility in water-based epoxy resin. In addition, the surface does not contain active imino groups and cannot undergo curing reaction with the epoxy resin. The toughening effect is poor, the friction mass loss of the epoxy resin paint film is large, the wear resistance is poor, and the pencil hardness is low. At the same time, the tensile strength, elongation at break and impact strength of the epoxy resin casting are low.
[0053] In Comparative Example 3, the polyester fiber is modified by radiation grafting with sodium 4-styrenesulfonate, and hydrophilic sulfonate groups are introduced on the surface of the polyester fiber, thereby improving the dispersibility of the polyester fiber in the water-based epoxy resin. The friction mass loss of the epoxy resin paint film is lower than that of Comparative Examples 1 and 2, and the hardness, tensile strength, elongation at break and impact strength are higher. However, it does not contain active imino groups and cannot undergo a curing reaction with the epoxy resin. The toughening effect is weaker than that of the embodiments, resulting in lower mechanical properties than those of the embodiments.
[0054] Although embodiments of the present invention have been shown and described, it will be appreciated by those skilled in the art that various changes, modifications, substitutions and variations may be made to the embodiments without departing from the principles and spirit of the present invention, and that the scope of the present invention is defined by the appended claims and their equivalents.
Claims
1. A method for preparing an environmentally friendly wear-resistant water-based coating, characterized in that: The preparation method comprises the following steps: Step (1), placing the cleaned and dried polyester fiber in ethanol, stirring, adding benzophenone and styrene sulfonate imide monomer, placing under ultraviolet light, carrying out grafting reaction in a nitrogen atmosphere, filtering, washing with xylene, ethanol and water in sequence, and drying to obtain modified polyester fiber; The styrene sulfonic acid imide monomer has the following structural formula (I): Step (2), adding water-based epoxy resin, modified polyester fiber, defoamer, thickener, pigment filler and dispersant into water, and then dispersing to obtain environmentally friendly wear-resistant water-based coating.
2. The method for preparing the environmentally friendly wear-resistant water-based coating according to claim 1, characterized in that: The power of the ultraviolet lamp in step (1) is 100-300W, and the wavelength is 360nm.
3. The method for preparing the environmentally friendly wear-resistant water-based coating according to claim 1, characterized in that: In the step (1), the mass of benzophenone and styrene sulfonic acid imide monomers are 1.2-2.6% and 20-40% of the mass of the polyester fiber, respectively.
4. The method for preparing the environmentally friendly wear-resistant water-based coating according to claim 1, characterized in that: The temperature of the grafting reaction in step (1) is 25-35° C. and the time is 20-40 minutes.
5. The method for preparing the environmentally friendly wear-resistant water-based coating according to claim 1, characterized in that: The mass of the modified polyester fiber in step (2) is 1-6% of the mass of the waterborne epoxy resin.
6. The method for preparing the environmentally friendly wear-resistant water-based coating according to claim 1, characterized in that: The preparation method of the styrene sulfonic acid imide monomer comprises: adding taurine and potassium hydroxide to methanol, adding 4-vinylbenzaldehyde after stirring, carrying out Schiff base reaction, adding precipitate to methanol after filtering, then adding potassium borohydride and water, carrying out reduction reaction, performing reduced pressure distillation, and recrystallizing the product in ethanol aqueous solution to obtain the styrene sulfonic acid imide monomer.
7. The method for preparing the environmentally friendly wear-resistant water-based coating according to claim 6, characterized in that: The molar ratio of taurine, potassium hydroxide, 4-vinylbenzaldehyde and potassium borohydride is 1:1:(0.9-1.1):(1.2-1.4).
8. The method for preparing the environmentally friendly wear-resistant water-based coating according to claim 6, characterized in that: The temperature of the Schiff base reaction is 50-60°C, and the reaction time is 3-4h; the temperature of the reduction reaction is 20-30°C, and the reaction time is 2-3h.
Citation Information
Patent Citations
Method for preparing polyester fiber reinforced epoxy composite material based on ultraviolet radiation modification
CN106317786A
Preparation method of waterborne epoxy antirust primer
CN109836956A
Water-based paint and preparation method thereof
CN114854285A
Wear-resistant waterproof epoxy anticorrosive paint and preparation method thereof
CN118308010A
Scalable synthesis of dipyrromethanes
US20050038262A1
Cited By
Wear-resistant thin-layer water-based paint and preparation method thereof
CN120310408A